Piptospatha teijsmannii a new species from Kepulauan Riau, Indonesia - Peter C., Boyce; Sin Yeng, Wong (Taylor & Francis Ltd., 2013)
A collection made in 1872 by Johannes Elias Teijsmann (J.E. Teijsmann 16705) on Pulau Lingga (Kepulauan Riau Province, Lingga Regency, Indonesia) has long been Piptospatha. Recent living collections have now shown that this collection is a taxonomic novelty, endemic to the Lingga Archipelago, and here described as Piptospatha teijsmannii. Piptospatha teijsmannii is morphologically most similar to Piptospatha ridleyi N.E.Br ex Hook.f., a species restricted to the Peninsular Malaysian states of Johor and Pahang, differing by the morphology of its flowers. Both P. teijsmannii and P. ridleyi are illustrated in colour, and differentiated with an identification key to the species of Piptospatha in Peninsular Malaysia and Lingga Regency. Speculation as to the possible evolutionary origin of P. teijsmannii is proffered.